Elastic Stability of Concentric Tube Robots Subject to External Loads - Ha, Junhyoung; Park, Frank C.; Dupont, Pierre E. (IEEE transactions on biomedical engineering, 2016)
Concentric tube robots, which are comprised of precurved elastic tubes that are concentrically arranged, are being developed for many medical interventions. The shape of the robot is determined by the rotation and translation of the tubes relative to each other, and also by any external forces applied by the environment. As the tubes rotate and translate relative to each other, elastic potential energy caused by tube bending and twisting can accumulate; if a configuration is not locally elastically stable, then a dangerous snapping motion may occur as energy is suddenly released. External loads on the robot also influence elastic stability. In this paper, we provide a second-order sufficient condition, and also a separate necessary condition, for elastic stability. Using methods of optimal control theory, we show that these conditions apply to general concentric tube robot designs subject to arbitrary conservative external loads. They can be used to assess the stability of candidate robot configurations. Our results are validated via comparison with other known stability criteria, and their utility is demonstrated by an application to stable path planning.